APPLICATION OF DIGITAL MARKETING TO MAX MEUBEL - Renny Christiarini; Febry Supriyanto (ConCEPt - Conference on Community Engagement Project, 2023)
This activity aims to carry out a digital marketing strategy to help promote products sold by a company to increase its sales revenue. This is due to the yearly increase in Instagram and TikTok users. Thus, the digital marketing platforms selected in this activity are Instagram and TikTok, which will be implemented from September to December 2022. The object of this activity is Max Meubel, which engages in the selling of furniture products. The data collection method in this activity uses interviews with the business owner and product documentation. After implementing the digital marketing strategy, there has been an increase in the sales and revenue of Max Meubel.